PENGARUH BEBAN KERJA, KETRAMPILAN KERJA DAN SIKAP KERJA TERHADAP KINERJA KARYAWAN SOTO MBAK LIN SEMARANG - Septian Rizky Dhaniswar, 13.05.51.0043; Yulianto, Heru (Students' Journal of Economic and Management, 2018)
Performance is defined as the result of a person's efforts achieved by the ability and deed in certain situations. Another opinion of performance is a result achieved by the worker in his work according to certain criteria applicable to a job. As for the population is Soto Mba Lin as many as 92 employees. the sample used is 92 respondents. Analyzer used is multiple linear regression The result of the research shows that job skill has positive and significant effect to employee performance. Workload has a positive and significant effect on employee performance. Work attitude has a positive and significant impact on employee performance. Keywords: work skills, workload, work attitude and employee performance